Residential Area Syndrome: Reasons for Non-Compliance in Motorcycling - Ganiem, Leila Mona (CV. Inara, 2021)
The motorcycle is the most used vehicle of transportation in developing countries. Driving a motorcycle has a very high risk of having an accident. One of the main causes of the accident is human behavior that violates the driving regulations. The interactions in the public space are close to nonverbal communication. Very little is understood about the rationale of driving behavior of motorcycle users, especially on the non-compliance behavior. The research objectives are to know what forms of non-compliance behaviors the motorcyclist has committed and to know how motorcyclists interpret non-compliance with motorbike riding. This is a phenomenological study, by observation, interviews, and secondary data collection. The total informants are 16 people between 12-60 years. The results show that the types of violations that riders have committed almost similar to the previous researches. The difference is about the driving against the traffic flow/incoming traffic that mentioned in almost all informants' statements and none of the informants studied stated that they were driving under the influence of alcohol or drugs. Motorcyclists interpret a motorbike as running water. The main finding of this research shows that Residential area syndrome that refers to the concept of proxemics is the reason for non-compliance behavior due to lack of knowledge and lack of supervision. A better understanding of the proxemics can create a better approach for communication to increase the compliance behavior in motorcycling to reduce the traffic accidents caused by human error.